Cd-substituted Mg composites with dual-equivalent permeability and permittivity for high-frequency miniaturization antennas. Issue 4 (March 2020) - Gan, Gongwen; Zhang, Dainan; Li, Jie; Wang, Gang; Huang, Xin; Yang, Yan; Rao, Yiheng; Xu, Fang; Wang, Xueying; Zhang, Huaiwu; Chen, Ray T.
Abstract: Spinel Mg ferrites Mg1-x Cdx Co0.05 Fe1.95 O4 (x=0.0, 0.2, 0.3 and 0.4) as potential agents for the miniaturization of high frequency antennas are presented. All the synthesized compositions were experimentally revealed to possess pure spinel phase. Dual-equivalent permeability and permittivity ( μ '≈26, ε '≈25, x=0.3 and μ '≈29, ε '≈28, x=0.4) from 5 to 100 MHz can be achieved by introducing Cd 2+ ions, yielding large miniaturization factors of up to 25 and 28. To figure out the effects of Cd 2+ ions substitution on magnetic and dielectric properties, the change in microstructure is mainly investigated. Meanwhile, enhanced magnetic properties including upward saturation magnetization ( Ms ) (approximately 47.60 emu/g) and reduced coercivity (approximately 54.22 Oe) are obtained due to increased grain size and denser microstructure arrangements reflected from scanning electron microscopy images. With low magnitude order of magnetic and dielectric losses factors ( tanδ ε reaches 10 -4, tanδ μ reaches 10 -2 ), the composites can potentially exhibit high operating efficiencies at high frequencies.